CdSe quantum dot-based nanocomposites for ultralow-power memristors - Bera, Jayanta; Betal, Atanu; Sharma, Ashish; Shankar, Uday; Rath, Arup Kumar; Sahu, Satyajit (ACS Applied Nano Materials, 2022)
The explosion in digital communication with the huge amount of data and the internet of things (IoT) led to the increasing demand for data storage technology with faster operation speed, high-density stacking, nonvolatility, and low power consumption for saving energy. Metal chalcogenide-based quantum dots (QDs) show excellent nonvolatile resistive memory behavior owing to their tunable electronic states and control in trap states by passivating the surface with different ligands. Here, we synthesized high-quality colloidal monodispersed CdSe QDs by the hot injection method. The CdSe QDs were blended with an organic polymer, poly(4-vinylpyridine) (PVP), to fabricate an Al\textbackslashCdSe-PVP\textbackslashAl device. Our device shows excellent bipolar nonvolatile resistive random access memory (RRAM) switching behavior with a high current ON/OFF ratio (I-ON/OFF) of 6.1 x 10(4), and it consumes ultralow power. The charge trapping and detrapping in the potential well formed by the CdSe QD and PVP combination result in resistive switching. This CdSe-PVP-based resistive random access memory (RRAM) device with a high I-ON/OFF, ultrafast switching speed, high endurance, low operating voltage, and long retention period can be used as a high-performance and ultralow-power memristive device.
Keywords: memory switching; memristor; metal chalcogenides; nonvolatile; quantum dots

Colloidal MoS2 quantum dots for high-performance low power resistive memory devices with excellent temperature stability - Bera, Jayanta; Betal, Atanu; Sharma, Ashish; Rath, Arup Kumar; Sahu, Satyajit (Applied Physics Letters, 2022)
Conventional memory technologies are facing enormous problems with downscaling, and are hence unable to fulfill the requirement of big data storage generated by a huge explosion of digital information. A resistive random access memory device (RRAM) is one of the most emerging technologies for next-generation computing data storage owing to its high-density stacking, ultrafast switching speed, high non-volatility, multilevel data storage, low power consumption, and simple device structure. In this work, colloidal MoS2 quantum dots (QDs) embedded in an insulating matrix of poly-(4vinylpyridine) (PVP) were used as an active layer to fabricate a RRAM device. The MoS2 QDs-PVP based RRAM device reveals an excellent nonvolatile resistive switching (RS) behavior with a maximum current on-off ratio (I-ON/I-OFF) of 10(5). High endurance, long retention time, and successive ``write-read-erase-read'' cycles indicate high-performance RRAM characteristics. The ultimate power consumption by this RRAM device is considerably low for energy saving. In addition, the MoS2 QDs-PVP based device shows RS behavior even at 130 degrees C. High I-ON/I-OFF, low operating power, high endurance, long retention time, and excellent stability with temperatures reveal that the MoS2 QDs-PVP based device can be a promising candidate for high-performance low power RRAM devices that can be operated at relatively higher temperatures. Published under an exclusive license by AIP Publishing.

Composition and surface morphology invariant high on-off ratio from an organic memristor - Betal, Atanu; Bera, Jayanta; Sharma, Ashish; Rath, Arup K.; Sahu, Satyajit (ACS Applied Electronic Materials, 2022)
Material composition plays a crucial role in the device performance; thus, nonvolatile memory devices from a small molecule named 5-mercapto-1-methyl tetrazole (MMT) in an insulating polymer matrix of poly(4-vinyl pyridine) (PVP) were fabricated. The composition of the active material in the device was varied to observe its influence on the device's electronic properties. The device with a more or less weight ratio of MMT has a much smoother surface morphology, whereas when the contributions of MMT and PVP were equal, the average surface roughness increased. However, the maximum on-off current ratio for all the devices is 10(5), suggesting that the MMT molecule does not show any change in its characteristic properties when surrounded by an insulating material. When the device was fabricated without the polymer matrix, the surface morphology of the device completely changed as it was filled with large holes. These holes provide short-circuited pathways for the current by forming the direct metal contact between the top and bottom electrodes. The carrier transport through these devices follows various conduction mechanisms. Some of the dominating conduction mechanisms are direct tunneling and trap-free and trap-assisted space-charge-limited conduction.
Keywords: Nonvolatile memory; Polymer; small molecule; space-charge; tunneling

Charge trapped CdS quantum dot embedded polymer matrix for a high speed and low power memristor - Betal, Atanu; Bera, Jayanta; Sharma, Ashish; Rath, Arup K. K.; Sahu, Satyajit (Physical Chemistry Chemical Physics, 2023)
The data storage requirement in the digital world is increasing day by day with the advancement of the internet of things. In this respect, nonvolatile resistive random-access memory is an option that provides high density and low power data storage capabilities. In this work, zero-dimensional colloidal CdS quantum dots and a polymer composite at an appropriate ratio were used to fabricate a memristive device. Comparison with a pristine CdS quantum dot-based device reveals that a surrounding matrix around the quantum dots is needed for observing memristive behavior. The quantum dots embedded in the polymer matrix device showed extremely stable electrical switching behavior that can be operated for more than 300 cycles and 60 000 seconds. Moreover, the device needs extremely low power to operate at a very high speed. The smooth surface morphology dictates a charge trapping mechanism for the switching phenomenon; however, an interplay between different charge transport mechanisms leads to the fast switching and high on-off ratio of the device.

Scanning tunneling microscopy investigation of synaptic behavior in AgInS2 quantum dots: effect of ion transport in neuromorphic applications - Betal, Atanu; Chetia, Anupam; Bera, Jayanta; Saikia, Dibyajyoti; Sharma, Ashish; Rath, Arup K.; Sahu, Satyajit (ACS Applied Nano Materials, 2024)
Scanning tunneling microscopy (STM) is a powerful technique for investigating the nanoscale properties of functional materials. Additionally, scanning tunneling spectroscopy (STS) facilitates the determination of the local density of states (LDOS) within the material. In this study, we present an exploration of the resistive switching (RS) properties and neuromorphic computing capabilities of individual AgInS2 quantum dots, utilizing STM and STS techniques. By examining the material's bandgap and its temperature dependence, we uncover a nonlinear variation below the Debye temperature and a linear trend at higher temperatures. Moreover, STS measurements demonstrate changes in the conducting states induced by localized pulses, further confirming the unique characteristics of the quantum dots. The experimental devices constructed by using these quantum dots effectively replicate the RS properties observed at the nanoscale. To assess the neuromorphic application of the devices, pulse transient measurements simulating the learning and forgetting processes were conducted. The gradual set and reset processes successfully mimic the information retention and erasure capabilities essential for neuromorphic computing. Notably, the resistive switching mechanism in these devices is attributed to localized ionic transport, which highlights the significant involvement of ionic species in the observed RS behavior. The outcomes of this study contribute to the fundamental understanding of RS properties in single AgInS2 quantum dots and offer valuable insights into their potential applications in neuromorphic computing.
Keywords: corona poling; Ion transport; neuromorphic computing; quantum dots; resistive switching; Scanning tunneling microscopy; STS

Air-stable double halide perovskite Cs2CuBiBr6: synthesis and memristor application - Betal, Atanu; Chetia, Anupam; Saikia, Dibyajyoti; Karmakar, Krishnendu; Bera, Ganesh; Dambhare, Neha V.; Rath, Arup K.; Sahu, Satyajit (Physical Chemistry Chemical Physics, 2025)
The excellent optical and electronic properties of halide perovskite materials have attracted researchers to investigate this particular field. However, the instability in ambient conditions and toxicity of materials like lead have given some setbacks to commercial use. To overcome these issues, perovskite-inspired materials with less toxic and excellent air-stable materials are being studied. Double perovskite materials are one of the perovskite materials. In this study, we have synthesized air-stable double perovskite Cs2CuBiBr6 using a solution process approach. The characterization of the material revealed that it has excellent crystallinity and high stability. The material shows excellent optical and electronic properties. It can be used in resistive memory devices. It shows stable current-voltage characteristics and analog switching. The ion migration through the active layer and accumulation of charge near the electrode region are the reasons behind the resistive switching.